PERKEMBANGAN MLU ANAK USIA 18 BULAN BERDASARKAN FREKUENSI INTERAKSI SOSIAL VERSUS GAWAI - Ni Kadek Devi Rahayu Padmayanti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study aims to analyze the language development of 18-month-old children with a focus on the Mean Length of Utterance (MLU) based on the frequency of social interactions and responses to gadgets. This study adopts a psycholinguistic approach, particularly Emergentist Approach (2022), to explain how competing language cues from social interaction and gadgets shape children's utterance development. Data were obtained from transcripts of children's utterances in the context of daily interactions with parents and when dealing with gadgets using a mixed-methods descriptive approach. The analysis was carried out by grouping word types using Kridalaksana's (2005) morphology theory and calculating the length of the number of morphemes per utterance, then averaging them to obtain the MLU value using Brown's (1973) theory. The research results show that six types of words were used during social interactions: nouns, verbs, numerals, adjectives, adverbs, interjection and variations of foreign languages were also found. Meanwhile, the responses to the gadgets only used two types of words: nouns and interjections. Furthermore, the development results the total MLU of children is at 1.64, which is included in the normal development stage according to the age range of 12–26 months according to Brown’s Stages of Language Development. If reviewed based on context, MLU in social interactions reaches 1.8, whereas MLU response to device is only 1.0. This shows that children are more capable of producing long, varied, and complex utterances when interacting with their parents or their environment, while responses to gadgets tend to be limited to single-word utterances or non-lexical vocalizations.